Patient-doctor relationships and its associated factors perceived by patients at non govermental hemodialysis clinics in Malaysia - Aziz, Ab Farid Fajilah Ab (2025)
Building strong patient-doctor relationships and effective communication are crucial for enhancing care quality and outcomes, particularly for hemodialysis patients. However, limited research exists on how these relationships impact patient outcomes in Malaysia, despite frequent interactions between hemodialysis patients and healthcare providers. This study aimed first to translate and validate the Malay versions of the Patient-Doctor Relationship Questionnaire and Doctor-Patient Communication Questionnaire, and subsequently to employ the validated tools to assess patient-doctor relationships and communication among hemodialysis patients in Malaysia. The study was conducted in two phases. In Phase I, expert panels translated and validated the PDRQ-9 and DPCQ into Malay. Cognitive debriefing involving eight hemodialysis care personnel and seven patients confirmed comprehensibility. Psychometric properties were assessed among 300 respondents using Confirmatory Factor Analysis (CFA) and internal consistency. The initialMyPDRQ demonstrated high internal consistency (Raykov’s rho=0.906), with CFA indices indicating good model fit (SRMR=0.025, RMSEA<0.001, CFI=1.000, TLI=1.000). The initialMyD-PCQ showed high reliability (Raykov’s rho=0.887) and good model fit (SRMR=0.037, RMSEA=0.029, CFI=0.982, TLI=0.979). In Phase II, a cross-sectional study using the validated MyPDRQ and MyD-PCQ was conducted among 640 hemodialysis patients across Malaysia. The majority were female (54.5%), aged 48 years or older (57.1%), Malay (47.0%), and married (58.8%). Nearly 60% had an income below RM 4360. The mean patient-doctor relationship score was 35.40 (SD=7.74), and the mean doctor-patient communication score was 51.09 (SD=8.14). Communication emerged as the most significant factor associated with relationships (Adj β=1.163, p<0.001). Younger patients (18–27 years) scored lower (Adj β=-0.044, p=0.027), while higher education levels were positively associated with better scores (Adj β=0.034, p=0.023). Employment and income were not statistically significant. The MyPDRQ and MyD-PCQ are valid and reliable instruments, providing appropriate tools for assessing patient-doctor relationships and communication among Malaysian hemodialysis patients. These findings have important implications for policy, practice, and future research, as they support the integration of culturally adapted measures into routine clinical care, inform targeted interventions to enhance communication, and contribute evidence for strategies aimed at improving long-term patient satisfaction and clinical outcomes